Steel rod tailing ultra-high performance concrete pole and manufacturing method thereof
By forming a dense aluminosilicate gel structure through modified alkali activator and activation modifier, combined with modified tailings sand and steel fiber, the environmental protection and high performance problems of tailings concrete poles are solved, and the preparation of low-energy consumption, high-strength steel rod tailings ultra-high performance concrete poles is realized.
Patent Information
- Application Number
- CN202511205761.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-08-27
AI Technical Summary
In the existing technology, tailings concrete materials have problems such as strong acidity and alkalinity, high salinity, poor soil structure, nutrient deficiency and heavy metal toxicity when used to prepare electric poles. In addition, the traditional cement preparation process has high energy consumption and large carbon emissions, making it difficult to achieve environmentally friendly and low-cost high-performance concrete pole production.
The method for making steel rod tailings ultra-high performance concrete poles is adopted. A dense aluminosilicate gel structure is formed by modified alkali activator and excitation modifier, and steel fiber and polyvinyl alcohol fiber are combined to form a multi-scale reinforcement network. Modified tailings sand is used to replace natural coarse and fine aggregates, simplifying the preparation process and reducing energy consumption.
It significantly improves compressive strength and fire resistance at room temperature, reduces environmental pollution, lowers energy consumption and carbon emissions, significantly improves early strength and crack resistance, toughness and impact resistance, and reduces equipment costs.
Smart Images

Figure CN120736832A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete poles, in particular to a steel bar tailings ultra-high performance concrete pole and a manufacturing method thereof. Background Art
[0002] Polymer raw materials contribute to the sustainable development of the construction industry. Polymers are formed by combining silicoaluminous raw materials and activators at room temperature or under certain curing conditions through a reaction process of "dissolution-monomer reconstruction-polycondensation," ultimately forming a new type of cementitious material with a zeolite-like structure. The "activator" can be an alkali silicate solution, sodium hydroxide, potassium hydroxide solution, or phosphoric acid solution. Its energy-saving and environmentally friendly properties during preparation give it significant advantages over ordinary Portland cement. It is widely used in building materials, fire-retardant coatings, fiber-reinforced composites, and the solidification of chemical contamination and radioactive waste. Therefore, it is considered the third generation of cement materials after lime and ordinary Portland cement.
[0003] Tailings commonly present problems such as high pH (strong acid or alkaline), high salinity, poor soil structure, nutrient deficiencies, and highly toxic heavy metals. The raw materials for tailings concrete are widely available and inexpensive, mostly industrial waste residues containing silica and aluminum minerals. Furthermore, the tailings concrete preparation process is simple, not requiring the "two grindings and one burning" process required for cement production, resulting in minimal waste. Compared to Portland cement, it can reduce carbon emissions by 80-90%, contributing to the achievement of energy-saving, environmentally friendly, and sustainable development. By replacing the natural coarse and fine aggregates in UHPC with tailings materials of varying particle sizes, a new concrete material with environmentally friendly, low cost, and excellent mechanical properties has been developed for the production of electric poles. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide a steel rod tailings ultra-high performance concrete pole and a manufacturing method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions: Steel rod tailings ultra-high performance concrete poles include the following components by mass: 551-641 parts of slag, 200-214 parts of fly ash, 45-50 parts of silica fume, 800-900 parts of modified tailings sand, 78-156 parts of steel fiber, 22-25 parts of borax (borax meets GB / T 537-2009 standard, content ≥95%), 359-425 parts of modified alkali activator, and 20-30 parts of polyvinyl alcohol fiber; The preparation of the modified base activator comprises the following steps: S21. In parts by mass, 45-50 parts of nano-lithium silicate were added to 140-145 parts by mass of 30% sodium hydroxide and ultrasonically dispersed at a frequency of 40kHz for 20-25min; S22. Sequentially add 10-15 parts of the excitation modifier, 3-5 parts of diethylenetriamine penta (methylene phosphonic acid), 0.3-0.5 parts of sodium gluconate to the solution obtained in step S21 and stir at a speed of 300-350r / min for 10-20min; S23. The mixed solution obtained in step S22 is stirred at 500 r / min in a water bath at 90-95°C for 1.5-2h and then cooled to 40-45°C to obtain a modified base activator.
[0006] Preferably, the preparation of the excitation modifier comprises the following steps: S221. In parts by mass, 35-40 parts of triethanolamine and 15-20 parts of polyetheramine were added to the reactor and stirred at 40-45 ° C at a speed of 300-350r / min for 10-15min to obtain a preliminary activator; S222. To the preliminary activator obtained in step S221, 12-15 parts of tetrabutyl titanate were slowly added at a rate of 1 mL / min. After the addition was complete, the temperature was raised to 75-80 ° C and the reaction was continued for 50-60 min to obtain a secondary activator. S223. Add 3-5 parts of γ-aminopropyltriethoxysilane and 17-20 parts of anhydrous ethanol to the secondary exciter, and continue the reaction at 55-60°C for 25-30 minutes to obtain an excitation modifier.
[0007] Preferably, the preparation of modified tailings sand comprises the following steps: S11. In parts by mass, 0.5-1 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.2-0.4 parts of mercaptopropylmethyldimethoxysilane were added to 20-22 parts of anhydrous ethanol, the pH was adjusted to 4-5 with acetic acid, and the silane modifier was obtained by hydrolysis for 25-30 min; S12 800-900 parts of tailings sand and 30-45 parts of tailings powder are mixed and dried at 100-105 ℃ for 1-2h to obtain a tailings mixture; S13. The silane modifier obtained in step S11 is sprayed onto the tailings mixture and stirred at a speed of 600-700 r / min for 10-15 min; S14. Add 0.1-0.3 parts of nano-cerium oxide to the mixture obtained in step S13, continue stirring for 15-20 minutes, and hot air cure at 75-80°C for 50-60 minutes to obtain modified tailings sand.
[0008] Preferably, the slag specific surface area is 430-450m 2 / kg, of which the silicon dioxide content is 33-35%, the calcium oxide content is 38-40%, and the remaining components are aluminum oxide.
[0009] Preferably, the specific surface area of silicon powder is 19600-19640m 2 / kg, of which the silicon dioxide content is 94-95%, and the rest is iron oxide.
[0010] Preferably, the steel fiber is straight, has a length of 11-15 mm, an equivalent diameter of 1-1.2 mm, and a tensile strength of ≥600 MPa.
[0011] Preferably, the tailings powder is the clinker of tailings sand after high-temperature calcination, with a mesh size of 200 meshes.
[0012] Preferably, the tailings sand is tailings waste collected from the tailings field, and is continuously graded, with a continuous particle size of 80-325 mesh, a silicon dioxide content of 60-65%, an aluminum oxide content of 10-20%, and the remaining components being iron oxide.
[0013] Preferably, the frequency of ultrasonic dispersion in step S21 is 40 kHz.
[0014] The method for manufacturing a steel rod tailings ultra-high performance concrete pole is used to manufacture the above-mentioned steel rod tailings ultra-high performance concrete pole, comprising the following steps: S1. In parts by mass, 551-641 parts of slag, 200-214 parts of fly ash, 45-50 parts of silicon fume are mixed and stirred at a speed of 200-300r / min for 15-20min to obtain the desired mixture; S2. The mixture obtained in step S1 and the modified tailings sand were mixed in a ratio of 1:1, 78-156 parts of steel fiber, 20-30 parts of polyvinyl alcohol fiber, 22-25 parts of borax and 359-425 parts of a modified alkali activator were added, and the mixture was mixed and stirred to obtain tailings concrete; S3. Pour the prepared concrete into a pole mold and vibrate it on a vibrating table for 3-5 minutes. After the mold is installed, the mold is cured at room temperature for 20-24 hours and then demolded. The demolded test block is placed in a curing box and cured at a relative humidity of 85-90% and a room temperature of 15-25°C for 7-8 days to obtain a steel rod tailings ultra-high performance concrete pole.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention can have high compressive strength under the condition of room temperature curing, simple production process, low environmental pollution, fire resistance and high temperature resistance and other excellent properties, greatly reducing energy consumption and equipment costs, making the production process more energy-efficient, significantly reducing natural sand and gravel mining and solid waste storage pollution, and the alkali-activated cementitious system replaces cement. Only the production of alkaline activated materials requires hot water mixing. The energy consumption of hot water accounts for about 10-20% of the total energy consumption of traditional cement, reducing carbon emissions in the production process by 80-90%, and reducing dust, SO2 and CO2 emissions from the source.
[0016] 2. The present invention forms a dense aluminosilicate gel structure through the synergistic effect of modified alkali activators and excitation modifiers, significantly improving the early strength, and at the same time forms a multi-scale reinforcement network with steel fibers and polyvinyl alcohol fibers to synergistically improve crack resistance, toughness and impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a flow chart of the preparation process of the present invention; Figure 2 This is a process flow chart for preparing the modified tailings sand of the present invention; Figure 3 The figure is a flow chart of the preparation process of the modified alkaline activator of the present invention; Figure 4 Flow chart of the preparation process of the excitation modifier of the present invention; Figure 5 The figure is a line graph showing the effect of the amount of modified tailings sand added on the compressive strength in Example 1 and Comparative Examples 2-4 of the present invention. DETAILED DESCRIPTION
[0018] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.
[0019] See also Figure 1-5 , the present invention provides a technical solution: Example 1 Manufacturing method of steel rod tailings ultra-high performance concrete pole: Before making steel rod tailings ultra-high performance concrete poles, the excitation modifier, modified alkali activator, and modified tailings sand are prepared: The preparation of the excitation modifier comprises the following steps: S221. 35 g of triethanolamine and 15 g of polyetheramine were added to the reactor and stirred at 40 ° C at a speed of 300 r / min for 10 min to obtain a preliminary activator; S222. 12 g of tetrabutyl titanate was slowly added to the preliminary activator obtained in step S221 at a rate of 1 mL / min. After the addition was complete, the temperature was raised to 75 ° C and the reaction was continued for 50 min to obtain a secondary activator. S223. 3 g of γ-aminopropyltriethoxysilane and 17 ml of anhydrous ethanol were added to the secondary exciter and the reaction was continued at 55 ° C for 25 min to obtain an excitation modifier; The preparation of the modified base activator comprises the following steps: S21. 45 g of nano-lithium silicate was added to 140 g of 25% sodium hydroxide and ultrasonically dispersed at a frequency of 40 kHz for 20 min; S22. Sequentially, 10 g of excitation modifier, 3 g of diethylenetriamine penta (methylene phosphonic acid), and 0.3 g of sodium gluconate were added to the solution obtained in step S21 and stirred at a speed of 300 r / min for 10 min; S23. The mixture obtained in step S22 was stirred in a water bath at 90 ° C for 1.5 h at a speed of 500 r / min and then cooled to 40 ° C to obtain a modified base activator; The preparation of modified tailings sand includes the following steps: S11. 0.5 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.2 g of mercaptopropylmethyldimethoxysilane were added to 20 ml of anhydrous ethanol, the pH was adjusted to 4 with acetic acid, and the mixture was hydrolyzed for 25 min to obtain a silane modifier; S12. 800g of tailings sand (silicon dioxide content of 60%, aluminum oxide content of 10%, iron oxide content of 30%) and 30g of tailings powder were mixed and dried at 100 ° C for 1h to obtain a tailings mixture; S13. The silane modifier obtained in step S11 is sprayed onto the tailings mixture and stirred at a speed of 600 r / min for 10 min; S14. 0.1 g of nano-cerium oxide was added to the mixture obtained in step S13, stirring was continued for 15 min, and hot air cured at 75 ° C for 50 min to obtain modified tailings sand; S1. 551g of slag (specific surface area 430m 2 / kg, of which the silicon dioxide content is 33%, the calcium oxide content is 38%, and the aluminum oxide content is 29%), 200g fly ash, 45g silica powder (specific surface area is 19600m 2 / kg, wherein the silicon dioxide content is 94% and the iron oxide content is 6%), and stirred at a speed of 200 r / min for 15 minutes to obtain the desired mixture; S2. The mixture obtained in step S1 and the modified tailings sand were mixed in a ratio of 1:1, 78g of steel fiber, 20g of polyvinyl alcohol fiber, 22g of borax and 359g of modified alkali activator were added, and the mixture was mixed and stirred to obtain tailings concrete; S3. Pour the prepared concrete into a pole mold and vibrate it on a vibrating table for 3 minutes. After the mold is installed, the mold is cured at room temperature for 20 hours and then demolded. The demolded test block is placed in a curing box and cured at a relative humidity of 85% and room temperature of 15°C for 7 days to obtain a steel rod tailings ultra-high performance concrete pole.
[0020] Example 2 Manufacturing method of steel rod tailings ultra-high performance concrete pole: Before making steel rod tailings ultra-high performance concrete poles, the excitation modifier, modified alkali activator, and modified tailings sand are prepared: The preparation of the excitation modifier comprises the following steps: S221. 40 g of triethanolamine and 20 g of polyetheramine were added to the reactor and stirred at 45 ° C at a speed of 350 r / min for 15 min to obtain a preliminary activator; S222. 15 g of tetrabutyl titanate was slowly added to the preliminary activator obtained in step S221 at a rate of 1 mL / min. After the addition was complete, the temperature was raised to 80 ° C and the reaction was continued for 60 min to obtain a secondary activator. S223. 5 g of γ-aminopropyltriethoxysilane and 20 ml of anhydrous ethanol were added to the secondary exciter, and the reaction was continued at 60 ° C for 30 min to obtain an excitation modifier; The preparation of the modified base activator comprises the following steps: S21. 50 g of nano-lithium silicate was added to 145 g of 30% sodium hydroxide and ultrasonically dispersed at a frequency of 40 kHz for 25 min; S22. Sequentially, 15g of the excitation modifier, 5g of diethylenetriamine penta(methylenephosphonic acid), and 0.5g of sodium gluconate were added to the solution obtained in step S21 and stirred at a speed of 350r / min for 20min; S23. The mixture obtained in step S22 was placed in a water bath at 95°C, stirred at a speed of 500 r / min for 2h, and then cooled to 45°C to obtain a modified base activator; The preparation of modified tailings sand includes the following steps: S11. 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.4-mercaptopropylmethyldimethoxysilane were added to 22 ml of anhydrous ethanol, the pH was adjusted to 5 with acetic acid, and the mixture was hydrolyzed for 30 min to obtain a silane modifier; S12. 900 g of tailings sand (silicon dioxide content of 65%, aluminum oxide content of 20%, iron oxide content of 15%) and 45 g of tailings powder were mixed and dried at 105 ° C for 2 h to obtain a tailings mixture; S13. The silane modifier obtained in step S11 is sprayed onto the tailings mixture and stirred at a speed of 700 r / min for 15 min; S14. 0.3 g of nano-cerium oxide was added to the mixture obtained in step S13, stirring was continued for 20 min, and hot air cured at 80 ° C for 60 min to obtain modified tailings sand; S1. 641g of slag (specific surface area of 450m 2 / kg, of which the silicon dioxide content is 35%, the calcium oxide content is 40%, and the aluminum oxide content is 25%), 214g fly ash, 50g silica fume (specific surface area is 19640m 2 / kg, wherein the silicon dioxide content is 95% and the iron oxide content is 5%), and stirred at a speed of 300 r / min for 20 min to obtain the desired mixture; S2. The mixture obtained in step S1 and the modified tailings sand were mixed in a ratio of 1:1, 156g of steel fiber, 30g of polyvinyl alcohol fiber, 25g of borax and 425g of modified alkali activator were added, and the mixture was mixed and stirred to obtain tailings concrete; S3. Pour the prepared concrete into a pole mold and vibrate it on a vibrating table for 5 minutes. After the mold is installed, the mold is cured at room temperature for 24 hours and then demolded. The demolded test block is placed in a curing box and cured at a relative humidity of 90% and room temperature of 25°C for 8 days to obtain a steel rod tailings ultra-high performance concrete pole.
[0021] Example 3 Manufacturing method of steel rod tailings ultra-high performance concrete pole: Before making steel rod tailings ultra-high performance concrete poles, the excitation modifier, modified alkali activator, and modified tailings sand are prepared: The preparation of the excitation modifier comprises the following steps: S221. 36 g of triethanolamine and 16 g of polyetheramine were added to the reactor and stirred at 41 ° C at a speed of 320 r / min for 11 min to obtain a preliminary activator; S222. 13 g of tetrabutyl titanate was slowly added to the preliminary activator obtained in step S221 at a rate of 1 mL / min. After the addition was complete, the temperature was raised to 76 ° C and the reaction was continued for 52 min to obtain a secondary activator. S223. 4 g of γ-aminopropyltriethoxysilane and 18 ml of anhydrous ethanol were added to the secondary exciter and the reaction was continued at 57 ° C for 26 min to obtain an exciter modifier; The preparation of the modified base activator comprises the following steps: S21. 46 g of nano-lithium silicate was added to 141 g of 26% sodium hydroxide and ultrasonically dispersed at a frequency of 40 kHz for 21 min; S22. Sequentially, 11g of excitation modifier, 4g of diethylenetriamine penta(methylenephosphonic acid), and 0.4g of sodium gluconate were added to the solution obtained in step S21 and stirred at a speed of 320r / min for 11min; S23. The mixture obtained in step S22 was stirred in a water bath at 91°C for 1.6 hours at a speed of 500 r / min and then cooled to 41°C to obtain a modified base activator; The preparation of modified tailings sand includes the following steps: S11. 0.6 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.3 g of mercaptopropylmethyldimethoxysilane were added to 21 ml of anhydrous ethanol, the pH was adjusted to 4.5 with acetic acid, and the mixture was hydrolyzed for 26 min to obtain a silane modifier; S12. 810 g of tailings sand (silicon dioxide content of 62%, aluminum oxide content of 13%, iron oxide content of 25%) and 35 g of tailings powder were mixed and dried at 101 ° C for 1.5 h to obtain a tailings mixture; S13. The silane modifier obtained in step S11 is sprayed onto the tailings mixture and stirred at a speed of 620 r / min for 11 min; S14. 0.2 g of nano-cerium oxide was added to the mixture obtained in step S13, stirring was continued for 16 min, and hot air curing was performed at 76 ° C for 52 min to obtain modified tailings sand; S1. 601g of slag (specific surface area 440m 2 / kg, of which the silicon dioxide content is 34%, the calcium oxide content is 39%, and the aluminum oxide content is 27%), 205g fly ash, 46g silica powder (specific surface area is 19610m 2 / kg, wherein the silicon dioxide content is 94.5% and the iron oxide content is 5.5%), and stirred at a speed of 220 r / min for 16 minutes to obtain the desired mixture; S2. The mixture obtained in step S1 and the modified tailings sand were mixed in a ratio of 1:1, 90g of steel fiber, 22g of polyvinyl alcohol fiber, 23g of borax and 380g of modified alkali activator were added, and the mixture was mixed and stirred to obtain tailings concrete; S3. Pour the prepared concrete into a pole mold and vibrate it on a vibrating table for 4 minutes. After the mold is installed, the mold is cured at room temperature for 21 hours and then demolded. The demolded test block is placed in a curing box and cured at a relative humidity of 86% and a room temperature of 17°C for 7 days to obtain a steel rod tailings ultra-high performance concrete pole.
[0022] Example 4 Manufacturing method of steel rod tailings ultra-high performance concrete pole: Before making steel rod tailings ultra-high performance concrete poles, the excitation modifier, modified alkali activator, and modified tailings sand are prepared: The preparation of the excitation modifier comprises the following steps: S221. 38 g of triethanolamine and 18 g of polyetheramine were added to the reactor and stirred at 44 ° C at a speed of 340 r / min for 14 min to obtain a preliminary activator; S222. 14 g of tetrabutyl titanate was slowly added to the preliminary activator obtained in step S221 at a rate of 1 mL / min. After the addition was complete, the temperature was raised to 79 ° C and the reaction was continued for 58 min to obtain a secondary activator. S223. 4.5 g of γ-aminopropyltriethoxysilane and 19 ml of anhydrous ethanol were added to the secondary exciter, and the reaction was continued at 59 ° C for 29 min to obtain an excitation modifier; The preparation of the modified base activator comprises the following steps: S21. 49 g of nano-lithium silicate was added to 144 g of 28% sodium hydroxide and ultrasonically dispersed at a frequency of 40 kHz for 24 min; S22. Sequentially, 14g of the excitation modifier, 4.5g of diethylenetriamine penta(methylenephosphonic acid), and 0.45g of sodium gluconate were added to the solution obtained in step S21 and stirred at a speed of 340r / min for 18min; S23. The mixture obtained in step S22 was stirred in a water bath at 94 ° C for 1.8 h at a speed of 500 r / min and then cooled to 44 ° C to obtain a modified base activator; The preparation of modified tailings sand includes the following steps: S11. 0.8 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.35 g of mercaptopropylmethyldimethoxysilane were added to 21 ml of anhydrous ethanol, the pH was adjusted to 4.5 with acetic acid, and the mixture was hydrolyzed for 28 min to obtain a silane modifier; S12. 880 g of tailings sand (silicon dioxide content of 64%, aluminum oxide content of 18%, iron oxide content of 18%) and 42 g of tailings powder were mixed and dried at 104 ° C for 1.5 h to obtain a tailings mixture; S13. The silane modifier obtained in step S11 is sprayed onto the tailings mixture and stirred at a speed of 680 r / min for 14 min; S14. 0.25 g of nano-cerium oxide was added to the mixture obtained in step S13, stirring was continued for 18 min, and hot air curing was performed at 79 ° C for 58 min to obtain modified tailings sand; S1. 630g of slag (specific surface area 440m 2 / kg, of which the silicon dioxide content is 34%, the calcium oxide content is 39%, and the aluminum oxide content is 27%), 211g fly ash, 48g silica fume (specific surface area is 19630m 2 / kg, wherein the silicon dioxide content is 94.5% and the iron oxide content is 5.5%), and stirred at a speed of 280 r / min for 18 minutes to obtain the desired mixture; S2. The mixture obtained in step S1 and the modified tailings sand were mixed in a ratio of 1:1, 142g of steel fiber, 28g of polyvinyl alcohol fiber, 24g of borax and 413g of modified alkali activator were added, and the mixture was mixed and stirred to obtain tailings concrete; S3. Pour the prepared concrete into a pole mold and vibrate it on a vibrating table for 4.5 minutes. After the mold is installed, the mold is cured at room temperature for 23 hours and then demolded. The demolded test block is placed in a curing box and cured at a relative humidity of 89% and room temperature of 24°C for 8 days to obtain a steel rod tailings ultra-high performance concrete pole.
[0023] Comparative Example 1 Comparative Example 1 differs from Example 1 in that no modified base activator is added in Comparative Example 1, and the remaining steps are exactly the same as those in Example 1.
[0024] Comparative Example 2 Comparative Example 2 differs from Example 1 in that the modified tailings sand is replaced with ordinary tailings sand in Comparative Example 2, and the remaining steps are exactly the same in Comparative Example 2 and Example 1.
[0025] Comparative Example 3 Comparative Example 3 differs from Example 1 in that the dosage of modified tailings sand in Comparative Example 3 is controlled to be 20%, and the remaining steps in Comparative Example 3 are exactly the same as those in Example 1.
[0026] Comparative Example 4 Comparative Example 4 differs from Example 1 in the following ways: the only difference is that the dosage of modified tailings sand in Comparative Example 4 is controlled to be 60%, and the remaining steps in Comparative Example 4 are exactly the same as those in Example 1.
[0027] Performance testing: According to the standard "GB / T 50081-2002 Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the performance test specimens of the steel bar tailings ultra-high performance concrete poles prepared in Examples 1-4 and Comparative Examples 1-2 after curing were tested. The results are shown in Table 1 below: Table 1
[0028] Comparative Example 1 and Comparative Example 2 did not add modified alkaline activator and modified tailings sand respectively. It can be seen from Table 1 that the compressive strength of Examples 1-4 is much greater than that of Comparative Example 1-2. The modified alkaline activator and modified tailings sand in the present invention play an important role in improving the compressive strength of the present invention.
[0029] Attachment Figure 5The following is a line graph showing the effect of the modified tailings sand dosage on compressive strength in Example 1 and Comparative Examples 2-4 of the present invention. The modified tailings sand dosage in Example 1 is 40%, in Comparative Example 2 it is 0%, in Comparative Example 3 it is 20%, and in Comparative Example 4 it is 60%. As can be seen from the graph, the compressive strength is highest when the modified tailings sand dosage is 40%, while the compressive strength of the unmodified tailings sand is lowest, demonstrating that the modified tailings sand of the present invention can effectively improve the compressive strength of steel rod tailings ultra-high performance concrete poles.
[0030] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. Steel rod tailings ultra-high performance concrete pole, characterized in that, The components include the following by mass: 551-641 parts of slag, 200-214 parts of fly ash, 45-50 parts of silica fume, 800-900 parts of modified tailings sand, 78-156 parts of steel fiber, 22-25 parts of borax and 359-425 parts of modified alkali activator, 20-30 parts of polyvinyl alcohol fiber; The preparation of the modified base activator comprises the following steps: S21. In parts by mass, 45-50 parts of nano-lithium silicate were added to 140-145 parts by mass of 25-30% sodium hydroxide and ultrasonically dispersed at a frequency of 40kHz for 20-25min; S22. Sequentially add 10-15 parts of the excitation modifier, 3-5 parts of diethylenetriamine penta (methylene phosphonic acid), 0.3-0.5 parts of sodium gluconate to the solution obtained in step S21 and stir at a speed of 300-350r / min for 10-20min; S23. The mixed solution obtained in step S22 is stirred at 500 r / min in a water bath at 90-95°C for 1.5-2h and then cooled to 40-45°C to obtain a modified base activator.
2. The steel rod tailings ultra-high performance concrete pole according to claim 1, characterized in that: The preparation of the excitation modifier comprises the following steps: S221. In parts by mass, 35-40 parts of triethanolamine and 15-20 parts of polyetheramine were added to the reactor and stirred at 40-45 ° C at a speed of 300-350r / min for 10-15min to obtain a preliminary activator; S222. To the preliminary activator obtained in step S221, 12-15 parts of tetrabutyl titanate were slowly added at a rate of 1 mL / min. After the addition was complete, the temperature was raised to 75-80 ° C and the reaction was continued for 50-60 min to obtain a secondary activator. S223. Add 3-5 parts of γ-aminopropyltriethoxysilane and 17-20 parts of anhydrous ethanol to the secondary exciter, and continue the reaction at 55-60°C for 25-30 minutes to obtain an excitation modifier.
3. The steel rod tailings ultra-high performance concrete pole according to claim 1, characterized in that: The preparation of the modified tailings sand comprises the following steps: S11. In parts by mass, 0.5-1 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.2-0.4 parts of mercaptopropylmethyldimethoxysilane were added to 20-22 parts of anhydrous ethanol, the pH was adjusted to 4-5 with acetic acid, and the silane modifier was obtained by hydrolysis for 25-30 min; S12 800-900 parts of tailings sand and 30-45 parts of tailings powder are mixed and dried at 100-105 ℃ for 1-2h to obtain a tailings mixture; S13. The silane modifier obtained in step S11 is sprayed onto the tailings mixture and stirred at a speed of 600-700 r / min for 10-15 min; S14. Add 0.1-0.3 parts of nano-cerium oxide to the mixture obtained in step S13, continue stirring for 15-20 minutes, and hot air cure at 75-80°C for 50-60 minutes to obtain modified tailings sand.
4. The steel rod tailings ultra-high performance concrete pole according to claim 1, characterized in that: The specific surface area of the slag is 430-450m 2 / kg, of which the silicon dioxide content is 33-35%, the calcium oxide content is 38-40%, and the remaining components are aluminum oxide.
5. The steel rod tailings ultra-high performance concrete pole according to claim 1, characterized in that: The specific surface area of the silicon powder is 19600-19640m 2 / kg, of which the silicon dioxide content is 94-95%, and the rest is iron oxide.
6. The steel rod tailings ultra-high performance concrete pole according to claim 1, characterized in that: The steel fiber is straight, has a length of 11-15 mm, an equivalent diameter of 1-1.2 mm, and a tensile strength of ≥600 MPa.
7. The steel rod tailings ultra-high performance concrete pole according to claim 3, characterized in that: The tailings powder is the clinker obtained after the tailings sand is calcined, and has a mesh size of 200 meshes.
8. The steel rod tailings ultra-high performance concrete pole according to claim 3, characterized in that: The tailings sand is tailings waste collected from a tailings field and is continuously graded with a continuous particle size of 80-325 meshes. The tailings sand has a silicon dioxide content of 60-65%, an aluminum oxide content of 10-20%, and the remaining components are iron oxide.
9. The steel rod tailings ultra-high performance concrete pole according to claim 1, characterized in that: The frequency of ultrasonic dispersion in step S21 is 40 kHz.
10. A method for manufacturing a steel rod tailings ultra-high performance concrete pole, for manufacturing the steel rod tailings ultra-high performance concrete pole according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. In parts by mass, 551-641 parts of slag, 200-214 parts of fly ash, 45-50 parts of silicon fume are mixed and stirred at a speed of 200-300r / min for 15-20min to obtain the desired mixture; S2. The mixture obtained in step S1 and the modified tailings sand were mixed in a ratio of 1:1, 78-156 parts of steel fiber, 20-30 parts of polyvinyl alcohol fiber, 22-25 parts of borax and 359-425 parts of a modified alkali activator were added, and the mixture was mixed and stirred to obtain tailings concrete; S3. Pour the prepared concrete into a pole mold and vibrate it on a vibrating table for 3-5 minutes. After the mold is installed, the mold is cured at room temperature for 20-24 hours and then demolded. The demolded test block is placed in a curing box and cured at a relative humidity of 85-90% and a room temperature of 15-25°C for 7-8 days to obtain a steel rod tailings ultra-high performance concrete pole.
Citation Information
Patent Citations
Hydrophobic modified alkali-activated inorganic polymer coating restoration material
CN104291741A
Cement-based material interface modifier, preparation method, aggregate, rebar and application thereof
CN109879633A
Modified component and application thereof as concrete carbonization modifier
CN117800634A
Alkali-activated iron tailing slag concrete and wave-dissipating self-locking block
CN118724558A
Hydrophobic antibacterial particle, preparation method thereof and application of hydrophobic antibacterial particle in real stone paint
CN119350906A
Cited By
Prestressed tailing concrete pole and manufacturing method thereof
CN121248257A
Prestressed tailings concrete poles and their manufacturing methods
CN121248257B